Human Immunodeficiency Virus Infection Increases the Risk of Incident Uveitis Among People Living With HIV/AIDS. (1st October 2018) - Yen, Yung-Feng; Feng, Jia-Yih; Yi-Fong Su, Vincent; Chuang, Pei-Hung; Ko, Ming-Chung; Chen, Chu-Chieh; Li, Yi-Jie; Pan, Sheng-Wei; Su, Wei-Juin
Abstract : Background: Case reports indicated that HIV itself may be a direct cause of uveitis. However, the association of HIV with incident uveitis has not been extensively studied. This nationwide cohort study determined the association of HIV with incident uveitis. Methods: Since January 1, 2003, we identified adult people living with HIV/AIDS (PLWHA) from Taiwan Centers for Disease Control HIV Surveillance Database. A control cohort without HIV infection, matched for age and sex, was selected for comparison from the Taiwan National Health Insurance Research Database. The time-dependent Cox proportional hazards model was used to determine the associations of HIV and highly active antiretroviral therapy (HAART) with incident uveitis, while considering death as a competing risk event. Results: Of the total 120, 430 patients (24, 086 PLWHA and 96, 344 matched controls), 609 (0.51%) had incident uveitis, including 334 (1.39%) PLWHA and 265 (0.28%) controls. After adjusting for age, sex, and comorbidities, HIV infection was found to be an independent risk factor for incident uveitis [adjusted hazard ratio (AHR), 5.55; 95% confidence interval (CI): 4.67 to 6.59]. Within PLWHA, the risk of incident uveitis was significantly higher in those who received HAART (AHR, 2.46; 95% CI: 1.71 to 3.54). In addition, considering the short- and long-term effects of HAART on incident uveitis, HAART was found to associate with a higher risk of uveitis development within 1 year of treatment (AHR, 3.36; 95% CI: 2.41 to 4.69), but not after 1 year of HAART initiation (AHR, 1.14; 95% CI: 0.76 to 1.72). Conclusions: HIV infection is an independent risk factor for incident uveitis. Abstract : Supplemental Digital Content is Available in the Text.